Integer programming formulation for convoy movement problem - Kumar, P. N. Ram. (2009)
This paper reports a study of the strategic network problem of routing military convoys between specific origin and destination pairs. Known as the Convoy Movement Problem (CMP), this problem is formulated as an integer linear program. The proposed mathematical model is evaluated on the basis of average number of iterations and average CPU times. LP-based lower bounds and heuristic based upper bounds were generated and used for evaluating the proposed model, particularly for large problem instances for which optimal solutions could not be obtained.